2008
DOI: 10.1038/nature06923
|View full text |Cite
|
Sign up to set email alerts
|

Midzone activation of aurora B in anaphase produces an intracellular phosphorylation gradient

Abstract: Proper partitioning of the contents of a cell between two daughters requires integration of spatial and temporal cues. The anaphase array of microtubules that self-organize at the spindle midzone contributes to positioning the cell division plane midway between the segregating chromosomes 1 . How this signaling occurs over micron length-scales, from the midzone to the cell cortex, is not known. Here we examine the anaphase dynamics of protein phosphorylation by Aurora B kinase, a key mitotic regulator, using F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
384
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(417 citation statements)
references
References 29 publications
31
384
1
1
Order By: Relevance
“…U2OS cells were transfected with a pIRESpuro2b vector containing H2B-targeted FRET sensor for Aurora B activity [24] and selected with 1 mg/ml puromycin (Sigma-Aldrich) for stable expression. HeLa and U2OS cells were grown in DMEM supplemented with 6% fetal bovine serum, pen/strep and l-glutamine (2 mM).…”
Section: Methodsmentioning
confidence: 99%
“…U2OS cells were transfected with a pIRESpuro2b vector containing H2B-targeted FRET sensor for Aurora B activity [24] and selected with 1 mg/ml puromycin (Sigma-Aldrich) for stable expression. HeLa and U2OS cells were grown in DMEM supplemented with 6% fetal bovine serum, pen/strep and l-glutamine (2 mM).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the reduced stiffness of centromeric chromatin in condensindepleted cells could create a gradient of tension: lowest near the surface of the centromere and progressively higher as the kinetochore is stretched further poleward. Because Aurora B activity is high on the chromosomes (Fuller et al, 2008), regions of lowered tension might be expected to favor kMT detachment and spindle checkpoint activation (King and Nicklas, 2000). Indeed, kinetochores undergoing excursions might be predicted to have particularly stable MT attachments, because they are located furthest from the Aurora B in the inner centromere (Cimini et al, 2006).…”
Section: Mitotic Delay In Condensin-depleted Cells Is Caused By Prolomentioning
confidence: 99%
“…[36][37][38] Once chromosomes become bi-oriented and tension is applied between sister kinetochores, Ndc80 moves away from Aurora B, resulting in kinetochoremicrotubule attachment stabilization. 39,40 Here we elaborate on recent studies that demonstrated a role of Dynein, 5 chromokinesins 5,41 and Aurora A kinase 5,41,42 in the prevention and correction of erroneous kinetochore-microtubule attachments during chromosome congression.…”
Section: Introductionmentioning
confidence: 99%